2006
DOI: 10.1128/ec.5.3.499-506.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cross Talk between a Fungal Blue-Light Perception System and the Cyclic AMP Signaling Pathway

Abstract: Blue light regulates many physiological and developmental processes in fungi. In Trichoderma atroviride the complex formed by the BLR-1 and BLR-2 proteins appears to play an essential role as a sensor and transcriptional regulator in photoconidiation. Here we demonstrate that the BLR proteins are necessary for carbon deprivation induced conidiation, even in the absence of light, pointing to the existence of an unprecedented cross talk between light and carbon sensing. Further, in contrast to what has been foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 51 publications
6
105
1
1
Order By: Relevance
“…(Casas-Flores et al, 2004;Castellanos et al, 2010;Purschwitz et al, 2008;Ruiz-Roldan et al, 2008;Schmoll, 2008). In Trichoderma atroviride the homologues of the WC proteins, the BLR proteins (blue light receptor 1 and 2), were shown to be necessary for blue light induced conidiation (Casas-Flores et al, 2004) and for carbon source dependent conidiation (Casas-Flores et al, 2006;Friedl et al, 2008a), which confirms a connection between light response and nutrient assimilation in fungi. Interestingly, also the photoreceptors of T. atroviride are involved in cellulase gene expression: Deletion of BLR-1 or BLR-2 causes strongly enhanced cellulase activities secreted into the culture medium (M. Friedl and M. Schmoll, unpublished).…”
Section: Light Positively Influences Cellulase Transcriptionsupporting
confidence: 48%
See 1 more Smart Citation
“…(Casas-Flores et al, 2004;Castellanos et al, 2010;Purschwitz et al, 2008;Ruiz-Roldan et al, 2008;Schmoll, 2008). In Trichoderma atroviride the homologues of the WC proteins, the BLR proteins (blue light receptor 1 and 2), were shown to be necessary for blue light induced conidiation (Casas-Flores et al, 2004) and for carbon source dependent conidiation (Casas-Flores et al, 2006;Friedl et al, 2008a), which confirms a connection between light response and nutrient assimilation in fungi. Interestingly, also the photoreceptors of T. atroviride are involved in cellulase gene expression: Deletion of BLR-1 or BLR-2 causes strongly enhanced cellulase activities secreted into the culture medium (M. Friedl and M. Schmoll, unpublished).…”
Section: Light Positively Influences Cellulase Transcriptionsupporting
confidence: 48%
“…Also for T. reesei cAMP is crucial in regulation of plant cell wall degrading enzymes: an early report showed an involvement of cAMP in regulation of cellulase gene expression (Sestak & Farkas, 1993) and is in accordance with the function of GNA3 in regulating cAMP levels and its function in this process ). For T. atroviride it was shown that the light response pathway crosstalks with the cAMP pathway (Friedl et al, 2008a;Casas-Flores et al, 2006) and in T. reesei, GNA3 as well as ENVOY have an effect on cAMP levels Tisch et al, 2011a). Therefore the cAMP pathway represents an important downstream regulatory pathway to be investigated for improvement of cellulase production.…”
Section: The Light Signalling Pathway and The Camp Pathway Are Intercmentioning
confidence: 99%
“…This result suggests that Tga3-mediated effects on conidiation are via a cAMP-independent pathway. It is also possible, as suggested by Casas-Flores et al (2006), that exogenous cAMP acts differently, through a cAMP receptor. In contrast, knockout mutations of tgaA (orthologue of tga1) and tgaB in T. virens do not differ from the wild-type in conidial phenotype (Mukherjee et al, 2004), and knockout mutants of gna1, a tga1 orthologue, in T. reesei are reduced or delayed in conidiation (Seibel et al, 2009).…”
Section: Heterotrimeric G Proteins and Map Kinase Cascadesmentioning
confidence: 99%
“…In dark-grown cells and light-adapted cells, protein kinase C (PKC) is thought to phosphorylate WC-1, thus modulating its activity . Casas-Flores et al (2006) suggested that PKA may be involved in the phosphorylation of BLR-1 following a light burst, thus stimulating transcription. Phosphorylation sites for both PKC and PKA are present in both WC-1 and BLR-1, which supports their assertion.…”
Section: Rapid Biochemical Changes Associated With Conidiationmentioning
confidence: 99%
“…Additionally, a number of biochemical and molecular data have provided support for the existence of yet another blue-light perception pathway. It appears that activation of both blue-light perception pathways is necessary for the regulation of photoconidiation (Berrocal-Tito et al, 2000;Rocha-Ramírez et al, 2002;Casas-Flores et al, 2006). Furthermore, the identification of light-regulated genes allowed us to identify red-lightregulated genes .…”
Section: Introductionmentioning
confidence: 99%